Gustometry in various variants of bronchial asthma: Sensitivity thresholds for bitter and sweet tast - V. N. Mineev; M. A. Nyoma; L. N. Sorokina; P. V. Bryukhanova; D. E. Koksharova (Медицинская иммунология, 2021)
The first studies were published on the possible pathogenetic role of so-called ectopically localized taste receptors in bronchial asthma. The receptors for bitter and sweet taste, may, apparently, have opposite functions, but in available literature there is no data on the balance of sensitivity for bitter and sweet tastes in the same patients with bronchial asthma. The aim of the present work is to simultaneously assess the sensitivity of canonical lingual receptors to bitter and sweet taste in the same patients with different clinical variants of bronchial asthma by methods applicable in wide clinical practice. 16 healthy persons and 35 patients with bronchial asthma were examined at the M.V. Chernorutsky Clinics of Hospital Therapy at First St. Petersburg State I. Pavlov Medical University. The sensitivity for bitter taste was assessed using The Frey Scientific 569885 PTC Taste Paper test strip kit containing phenylthiourea solution. Sucrose solutions at concentrations of 0.3; 0,4; 0,5; 0,6; 0,7; 0,8; 0,9 % for determination of individual value of taste thresholds to sweet taste were used. The bitter-to-sweet taste sensitivity balance was assessed on the basis of an original “bitter/sweet taste sensitivity” index. The highest values of index of bitter/sweet taste was found in the allergic variant of bronchial asthma: its values are significantly different from those in healthy persons only at low sucrose concentrations (0.3-0.4%). The factor analysis revealed an association between taste imbalance (a shift towards high sensitivity to sweet taste) and key characteristics of bronchial asthma, including severity of bronchial asthma course, duration of inhaled glucocorticosteroid use and inefficiency of β2-agonists use at pre-clinical stage. It has been revealed by gustometry that in the allergic variant of bronchial asthma there is a decreased sensitivity for bitter test substance (phenylthiourea), along with higher sensitivity for sweet taste (sucrose).